2020
DOI: 10.1111/gfs.12472
|View full text |Cite
|
Sign up to set email alerts
|

Establishment techniques affect productivity, nutritive value and atmospheric N2 fixation of two sunn hemp cultivars

Abstract: Grass Forage Sci. 2020;75:153-158. wileyonlinelibrary.com/journal/gfs | 153

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
4
12
0
Order By: Relevance
“…Jaramillo et al. (2020) showed annual N fixation of 41 and 25 kg N ha −1 yr −1 for Crescent Sunn and Blue Leaf, respectively, performing the study in North Florida. These genotypes had comparable HA to the values reported in the current study (Table 2), but less N fixation was exhibited.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Jaramillo et al. (2020) showed annual N fixation of 41 and 25 kg N ha −1 yr −1 for Crescent Sunn and Blue Leaf, respectively, performing the study in North Florida. These genotypes had comparable HA to the values reported in the current study (Table 2), but less N fixation was exhibited.…”
Section: Discussionmentioning
confidence: 85%
“…Cherr, Scholberg, and McSorley (2006), evaluated sunn hemp performance as a green manure in central Florida and reported HA of 4.0 Mg DM ha −1 at 60 d after seeding. In northern Florida, Jaramillo et al (2020) reported a HA of 1.7 and 3.2 Mg DM ha −1 for Blue Leaf and Crescent Sunn, respectively, at 60 d after seeding. Conversely, CP concentrations decreased as HA increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations